2018
DOI: 10.1016/j.apenergy.2017.11.085
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of condensation of sulfuric acid and water in a large two-stroke marine diesel engine

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…7,39 The condensation of H 2 SO 4 occurs in the gas phase just before reaching the lube oil film, where the temperature is lower than in the bulk gas phase. 6,47,48,56 Since no mixing is occurring, transport of CaCO 3 micelles to the H 2 SO 4 happens by diffusion. However, when the piston moves towards TDC (compression stroke, Figure 9(c)), the piston rings act to spread and remove excess lube oil from the cylinder liner.…”
Section: Application Of the Mfr Model To Conditions In A Large Two-stmentioning
confidence: 99%
See 2 more Smart Citations
“…7,39 The condensation of H 2 SO 4 occurs in the gas phase just before reaching the lube oil film, where the temperature is lower than in the bulk gas phase. 6,47,48,56 Since no mixing is occurring, transport of CaCO 3 micelles to the H 2 SO 4 happens by diffusion. However, when the piston moves towards TDC (compression stroke, Figure 9(c)), the piston rings act to spread and remove excess lube oil from the cylinder liner.…”
Section: Application Of the Mfr Model To Conditions In A Large Two-stmentioning
confidence: 99%
“…Depending on the operating conditions, different concentrations of the H 2 SO 4 droplets can condense onto the lube oil film in a real engine application. 56 The range from concentrated (18·10 3 mol m -3 ) to very dilute H 2 SO 4 droplets (1.8·10 3 mol m -3 ) is therefore examined. Wu et al 21 found that the shrinking rate of acid droplets depends on the lube oil formulation, i.e.…”
Section: Parametric Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The conversion may, however, be more than 4% in large low‐speed marine engines partly because of much lower engine speeds. In addition, advanced computational efforts indicate that H 2 SO 4 vapours will condense on the cylinder liners …”
Section: Introductionmentioning
confidence: 99%
“…In addition, advanced computational efforts indicate that H 2 SO 4 vapours will condense on the cylinder liners. 19,20 Cylinder lubrication oils used in large two-stroke marine engines contain alkaline additives (primarily CaCO 3 ) that neutralise acids. [21][22][23][24] The content of alkaline constituents is defined by the base number (BN).…”
Section: Introductionmentioning
confidence: 99%